2007
DOI: 10.1016/j.tube.2007.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Co-infection with human immunodeficiency virus and tuberculosis in Asia

Abstract: Asia has had historically high levels of tuberculosis (60% of the global total) and has experienced a marked rise in HIV seroprevalence (22% of the global total) in key subpopulations of these highly populous nations. Thus, co-infected patients are a challenge for practitioners and public health workers alike. The U.S.-Japan Cooperative Medical Science Program is spearheading interdisciplinary collaborations in Asia to address the many outstanding research priorities for HIVtuberculosis co-infection. There is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 113 publications
0
16
0
2
Order By: Relevance
“…National HIV/AIDS reports in China showed that 29.4% of all new HIV infection cases in 2011were among MSM, up from 12.2% in 2007[1], [2]. HIVprevalence among MSM is particularly high in some large Chinese cities, for example ranging between 5.1–9.9% in Beijing (the capital city in northeastern China) [3][5], and 8.5–16.8% in Chongqing, a metropolitan city in southwestern China [6]–[8]. MSM are not only passively impacted by HIV infection, but are also an important driver of the broader HIV epidemic.…”
Section: Introductionmentioning
confidence: 99%
“…National HIV/AIDS reports in China showed that 29.4% of all new HIV infection cases in 2011were among MSM, up from 12.2% in 2007[1], [2]. HIVprevalence among MSM is particularly high in some large Chinese cities, for example ranging between 5.1–9.9% in Beijing (the capital city in northeastern China) [3][5], and 8.5–16.8% in Chongqing, a metropolitan city in southwestern China [6]–[8]. MSM are not only passively impacted by HIV infection, but are also an important driver of the broader HIV epidemic.…”
Section: Introductionmentioning
confidence: 99%
“…TB up-modulates the host immune system; a T-cell that is activated in response to infection from M. tuberculosis produces more HIV than a quiescent cell; HIV expression increases in the face of coinfections. The high HIV viral load increases the rate of disease progression, which in turn increases HIV infectiousness [11].…”
Section: Discussionmentioning
confidence: 99%
“…There is a much greater risk of HIV/TB co-infected patients developing active TB, either from the latent infection being reactivated or due to the rapid progression of a new infection [10][11][12][13]. The risk of developing active TB in HIV patients increases from 5 to 15% annually, due to the latent infection being reactivated; this depends on the degree of immunocompromise [12,14,15].…”
mentioning
confidence: 99%
“…Exemplary is the case of the interaction that occurs between the zoonotic diseases tuberculosis and HIV infection, two significant threats to health that increasingly are found entwined, with adverse health consequences in low-income and otherwise disadvantaged populations (Burke 2011;Cohen et al 2010;Geldmacher, Zumla, and Hoelscher 2012;Vermund and Yamamoto 2007). The first of these syndemic partners, tuberculosis, is most common in "populations rendered susceptible by instability of residence [and overcrowding], mixing of populations, forced migration, breakdown of government and social institutions that provide order and protection, major life-threatening events, poor sanitation, high rates of certain other diseases, [and] exposure to chemicals and particles which irritate the deep lung" (Wallace and Wallace 1998:84).…”
Section: Troubles Never Come Alone: Syndemics Ecosyndemics and Medimentioning
confidence: 99%